Uji Aktivitas Antijamur Bacillus cereus terhadap Colletotrichum fructicola KRCR Penyebab Penyakit Antraknosa pada Buah Cabai Rawit (Capsicum frutescens L.) - KRISNA SANUBARI PURBA; KHAMDAN KHALIMI; NI WAYAN SUNITI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Test of Antifungal Activity of Bacillus cereus Against Colletotrichum fructicola Causing Anthracnose Disease in Cayenne Pepper (Capsicum frutescent L.) Anthracnose or fruit rot disease that attacks ceyenne pepper is caused by the pathogenic fungus Colletotrichum fructicola, this disease can cause crop failure. Currently, control of this disease is still using synthetic fungicides, but this method can cause demage to the ecosystem. Biopesticides are one of the enviromentally friendly control of plant phatogens because biopesticides use biologycal agents. The purpose of this study was to determine the ability of B. cereus bacteria to inhibit the growth of C. fructicola KRCR cause anthracnose desease in vitro. The result showed that bacteria B. cereus was able to inhibit the growth of fungal colonies C. fructicola KRCR on potato dextrose agar (PDA) with an inhibitory percentage of 90.55% when compared to controls. The results of the B. cereus filtrate test a concentration of 50% is able to inhibit the growth of C. fructicola KRCR with an inhibitory percentage of 87.56%.